Analysis of periosteal lesions from commingled human remains at the Xagħra Circle hypogeum reveals the first case of probable scurvy from Neolithic Malta. (15th September 2021) - Thompson, Jess E.; Power, Ronika K.; Mercieca‐Spiteri, Bernardette; Magnussen, John S.; Pardey, Margery; Buck, Laura T.; Stock, Jay T.; McLaughlin, T. Rowan; Stoddart, Simon; Malone, Caroline
Abstract: Objectives: Palaeopathological analysis is key for characterising population health at the individual level and across large assemblages but is rarely exploited to unite the remains of disarticulated individuals. This study explores the potential for individual identification through differential diagnosis of periosteal lesions in a commingled deposit, both to ascertain the number of individuals represented and provide a differential diagnosis. Materials and Methods: The late Neolithic Xagħra Circle hypogeum on Gozo contains the remains of more than 800 individuals, most of which were transformed to a collective disarticulated assemblage. Across the excavated population, pathological observations are strikingly low. In one specific 1 × 1‐m area in a single stratigraphic context, fragmented and disarticulated cranial and post‐cranial non‐adult bones were identified that displayed periosteal new bone formation. To aid differential diagnosis, macroscopic analysis, taphonomic analysis and micro‐computed tomography (μCT) imaging were integrated. Results: This approach, when combined with osteobiographical analyses, reveals that the elements most likely derive from one individual, a young child, who presents a probable case of scurvy. The potential for micronutrient co‐morbidities are explored, but without further microscopic study it cannot be determined if this individual also experienced iron‐deficiency anaemia and/or rickets. Discussion: In the context of the Mediterranean and Europe in later prehistory, reported cases of scurvy are currently low and often reveal periods of environmental instability and resource insufficiency. Our finding of non‐adult scurvy in late 3rd millennium BC Malta contributes to a developing picture of an increasingly unstable palaeoenvironment and declining population health at this time, although it may also indicate an individual case of poor childhood health within this broader context.